Measurement of esophago‐gastric junction cross‐sectional area and distensibility by an endolumenal functional lumen imaging probe for the diagnosis of gastro‐esophageal reflux disease. Issue 11 (26th August 2013) - Tucker, E.; Sweis, R.; Anggiansah, A.; Wong, T.; Telakis, E.; Knowles, K.; Wright, J.; Fox, M.
Abstract Background Measurement of esophago‐gastric junction (EGJ) cross‐sectional area (CSA) and distensibility by an Endolumenal Functional Lumen Imaging Probe (EndoFLIP®) may distinguish between gastro‐esophageal reflux disease (GERD) patients and healthy volunteers (HV). We aimed to assess the agreement of EndoFLIP® measurements with clinical and physiologic diagnosis of GERD. Methods Twenty‐one HV and 18 patients with typical GERD symptoms were studied. After gastroscopy, EGJ CSA, and distensibility were measured by EndoFLIP®. Forty‐eight hour esophageal pH monitoring was then performed by a wireless system. The ability of EndoFLIP® to discriminate GERD patient and HVs was assessed. Planned secondary analysis then assessed whether EGJ CSA and distensibility were increased in individuals with pathologic acid exposure. Key Results Healthy volunteers were younger and had lower body mass index (BMI; both p < 0.001). Pathologic acid exposure was present in 3/21 (14%) HVs and 9/18 (50%) patients (p = 0.126). At 30 mL EndoFLIP® bag volume, EGJ CSA was higher (p = 0.058) and EGJ distensibility was lower (p = 0.020) in HVs than patients. Secondary analysis showed that EGJ measurements were similar in participants with and without pathologic acid exposure (CSA 98 mm2vs 107 mm2; p = 0.789, distensibility; p = 0.704). An inverse association between BMI and CSA (R2 = 0.2758, p = 0.001) and distensibility (R2 = 0.2005, p = 0.005) was present. Conclusions & Inferences Endolumenal Functional Lumen Imaging Probe is not useful for GERD diagnosis because EGJ CSA and distensibility do not distinguish between HVs and GERD patients defined by clinical presentation or pH measurement. This unexpected result may be due to an important, confounding interaction of obesity.